Copper Tolerance Mediated by FgAceA and FgCrpA in Fusarium graminearum - Liu, Xin; Jiang, Yichen; He, Dan; Fang, Xin; Xu, Jianhong; Lee, Yin-Won; Keller, Nancy P.; Shi, Jianrong (Frontiers in Microbiology, 2020)
All organisms must secure essential trace elements (e.g., Cu) for survival and reproduction. However, excess trace element accumulation in cells is highly toxic.The maintenance of copper (Cu) homeostasis has been extensively studied in mammals, bacteria, and yeast but not in plant pathogens. In this study, we investigated the molecular mechanisms of copper tolerance in Fusarium graminearum, the important wheat head scab fungus. RNA-Seq revealed induced expression of the P-type ATPase transporter FgCrpA and metallothionein (MT) FgCrdA after excess Cu treatment. Deletion of FgCrpA but not FgCrdA resulted in reduced tolerance to Cu toxicity. The "Cu fist" transcription factor FgAceA was involved in Cu detoxification through activation of FgCrpA. △FgAceA was more sensitive to copper toxicity than △FgCrpA and overexpression of FgCrpA restored copper tolerance in △FgAceA.FgAceA negatively regulated aurofusarin production and its biosynthetic gene expression. △FgCrpA and △FgAceA were reduced in virulence in flowering wheat heads and synthesized decreased amounts of the mycotoxin deoxynivalenol when challenged with excess Cu. Taken together, these results suggest that mediation of Cu tolerance in F. graminearum mainly relies on the Cu efflux pump and that FgAceA governs Cu detoxification through activation of FgCrpA.